Fraudulent Investments from the Perspective of Criminal Law and Islamic Law - Rafi Arnanda Faturohman; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Fraudulent investment is a serious threat to the people of Indonesia, massive technological developments have indeed had many positive impacts but there have also been negative impacts arising from these technological developments. Fraudulent investment is one of the negative impacts of these technological developments. This development makes investment or trading activities possible for anyone at any time, the rise of investment types offered to the public through public figures that are not accompanied by references to investment‐related literacy is one of the factors in the many victims of fraudulent investment in Indonesia.